MANAGEMENT OF BANK LOANS FOR MICRO, SMALL AND MEDIUM-SIZED MARKETING PERSPECTIVE AND IN TERMS OF LEGALITY IN ITS DISTRIBUTION AND ITS IMPACT ON ECONOMIC DEVELOPMENT AND LABOR ABSORPTION - Wibowo, Sampurno; Hidayat, Agus Maolana; Arwiyah, H M Yahya (International Journal of Education, 2010)
This study focuses on the development value of sales, labor on ict companies in Bandung, the output value of industry sector and subsector telecommunications equipment industry, exports of communications including communications telecommunications equipment industry, as well as economic development, employment and bank lending in the form of small and medium-sized micro-credit for the years 2000 - 2008 to kabupatenkota in West Java province. Results obtained bank loan facilities for the industrial sector and the inflation rate together to have a significant impact on employment in West Java, on changes in bank lending as a whole no significant influence on the change of value of output and employment in the industry as a whole and telecommunications equipment industry,Â  exports of communications and telecommunications equipment communications in western Java, while the UMKM loans to agriculture, mining, processing industry, trade, hotels and restaurants, transport and communication co, construction, service businesses, community social services, and other sectors together have a significant effect on employment in western Java. So that banking institutions should give greater credit to sectors of the productive economy, and have a wider effect multipier between sectors, so the increase in credit for UMKM will positively impact employment in west Java, so does the local government to provide certainty law for licensing services, transparency, and lower cost, especially for UMKM to various economic sectors in western Java.